High-Stakes Testing and the History of Graduation - Dorn, Sherman (Education Policy Analysis Archives, 2003)
An historical perspective on high-stakes testing suggests that tests required for high school graduation will have mixed results for the putative value of high school diplomas: (1) graduation requirements are likely to have indirect as well as direct effects on the likelihood of graduating; (2) the proliferation of different exit documents may dilute efforts to improve the education of all students; and (3) graduation requirements remain unlikely to disentangle the general cultural confusion in the U.S. about the purpose of secondary education and a high school diploma, especially confusion about whether the educational, exchange, or other value of a diploma is most important.